A Comparative Study of Henry Giroux and Robert Floden’s Educational Thoughts for Developing a Model for Philosophy of Teacher Education - Aboosaeed Davarpanah (Comparative Education Society of Iran ( CESIR), 2021)
The aim of present study is a comparative investigation of two famous philosophers, Henry Giroux and Robert Floden, to develop a model for the philosophy of teacher education. The research method is qualitative with inferential-analytical approach. As a supporter of change, interaction, democracy, and transformation, Giroux emphasizes on training of teachers who are familiar with reflective interaction and its use. Floden also emphasizes the cultivation of a pragmatic teacher who is familiar with theoretical foundations and is an interactive, creative expert, and non-dominant person. From the perspective of the two philosophers, it can be inferred that the ideal teacher is one who believes in reflective interactions and avoidance in the field of education and emphasizes reform in the shadow of accepting "other". Based on the intellectual foundations of these two thinkers, a model has been designed to show the process of training an ideal teacher